Planeación estratégica the white label restaurant (2023)
This thesis work focuses on conducting simulations of three different scenarios for the SAVORA restaurant, with the aim of evaluating its performance in a competitive environment and analyzing the strategic decisions necessary to achieve success in the market. The scenarios are distinguished by variations in the strength of the competition and the timing of its entry into the market. To achieve the set objectives, various variables that could be modified throughout the simulation were considered, such as dish prices, maintenance expenses, staff, marketing, menu updates, and capital requests.